γδ T cells recognize the insulin B:9-23 peptide antigen when it is dimerized through thiol oxidation() - Aydintug, M. Kemal (2014)
The insulin peptide B:9-23 is a natural antigen in the non-obese diabetic (NOD) mouse model of type 1 diabetes (T1D). In addition to αβ T cells and B cells, γδ T cells recognize the peptide and infiltrate the pancreatic islets where the peptide is produced within β cells. The peptide contains a cysteine in position 19 (Cys19), which is required for the γδ but not the αβ T cell response, and a tyrosine in position 16 (Tyr16), which is required for both. A peptide-specific mAb, tested along with the T cells, required neither of the two amino acids to bind the B:9-23 peptide. We found that γδ T cells require Cys19 because they recognize the peptide antigen in an oxidized state, in which the Cys19 thiols of two peptide molecules form a disulfide bond, creating a soluble homo-dimer. In contrast, αβ T cells recognize the peptide antigen as a reduced monomer, in complex with the MHCII molecule I-A(g7). Unlike the unstructured monomeric B:9-23 peptide, the γδ-stimulatory homo-dimer adopts a distinct secondary structure in solution, which differs from the secondary structure of the corresponding portion of the native insulin molecule. Tyr16 is required for this adopted structure of the dimerized insulin peptide as well as for the γδ response to it. This observation is consistent with the notion that γδ T cell recognition depends on the secondary structure of the dimerized insulin B:9-23 antigen.